Wolf Island - Shan, Darren (New York : Little Brown, 2009)
As the mysterious Shadow builds an army of demons, Grubbs Grady and his team search desperately for answers. But when they follow up on a new lead, it takes them to an old, unexpected foe-- the Lambs.
Keywords: Demonology -- Juvenile fiction; Werewolves -- Juvenile fiction; Demonology -- Fiction; Werewolves -- Fiction; Horror stories